2014
DOI: 10.1111/acem.12511
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fat Emulsion on Hemodynamics Following Treatment With Propranolol and Clonidine in Anesthetized Rats

Abstract: Objectives: There is evidence indicating that intravenous fatty emulsion (IFE) is beneficial in restoring circulatory function in certain types of drug overdose. The authors investigated the hemodynamic effects of IFE compared to epinephrine in rats treated with propranolol and clonidine.Methods: Anesthetized male Sprague-Dawley rats were instrumented for measurement of hemodynamics. Rats were randomly assigned to one of six groups (n = 6-8), and each received a clonidine infusion (150 lg/kg) or an equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Each rat received a bolus dose of propranolol (15 mg/kg IV; administered over two minutes); this dose of propranolol invariably causes hypotension and eventual cardiovascular collapse without intervention. [ 16 ] Immediately following propranolol administration, rats were given either Intralipid 20% (1 mL/kg [n = 9], 2 mL/kg [n = 6], or 3 mL/kg [n = 6] IV) or ClinOleic 20% (1 mL/kg [n = 8], 2 mL/kg [n = 6], or 3 mL/kg [n = 6] IV), or saline (1 mL/kg [n = 4]) as a bolus over a 30 second period. The starting dose of ILE (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each rat received a bolus dose of propranolol (15 mg/kg IV; administered over two minutes); this dose of propranolol invariably causes hypotension and eventual cardiovascular collapse without intervention. [ 16 ] Immediately following propranolol administration, rats were given either Intralipid 20% (1 mL/kg [n = 9], 2 mL/kg [n = 6], or 3 mL/kg [n = 6] IV) or ClinOleic 20% (1 mL/kg [n = 8], 2 mL/kg [n = 6], or 3 mL/kg [n = 6] IV), or saline (1 mL/kg [n = 4]) as a bolus over a 30 second period. The starting dose of ILE (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…1 mL/kg) was based on our previous work demonstrating Intralipid 20% could reverse the hypotension and prevent the cardiovascular collapse associated with this dose of propranolol. [ 16 ] Following return to baseline blood pressure, rats were monitored for up to two hours following ILE administration, at which time surviving rats were euthanized by isoflurane overdose and excision of the heart. Rats that lived for 120 minutes post-propranolol administration were considered as survivors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another group of drugs that pose a risk of overdose, particularly in elderly populations, are cardiac medications, especially β‐blockers and calcium channel blockers. Overdoses with β‐blockers, propranalol 108 , 132 134 and metoprolol 107 , 114 , 135 , 136 have been treated with LRT. However, animal studies have not demonstrated similarly promising results.…”
Section: Part Iii: Clinical Futurementioning
confidence: 99%